The excavations at Khirbet el-Maqatir : 1995-2001 and 2009-2016. - Stripling, Scott, (Archaeopress Archaeology, 2023)
Khirbet el-Maqatir lies 16 km north of Jerusalem. The Associates for Biblical Research excavated 14 summer seasons and 5 winter seasons between 1995 and 2016. Volume 2 reports on the remains of a Late Hellenistic/Early Roman village, and a Byzantine ecclesiastical complex.